2015
DOI: 10.1093/cid/civ910
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Tuberculosis Treatment Outcomes in Relation to Treatment and Initial Versus Acquired Second-Line Drug Resistance

Abstract: Increasing drug resistance was associated in a logical stepwise manner with poor treatment outcomes. Acquired resistance was worse than initial resistance to the same drugs. Increasing numbers of effective drugs, specific drugs, and specific program characteristics were associated with better outcomes and less acquired resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 19 publications
5
63
0
1
Order By: Relevance
“…In the case of rifampin, a prior study found that phenotypic DST does not capture some clinically relevant resistance conferred by disputed rpoB mutations that had previously been considered of indeterminate significance; these were associated with a rate of failure or relapse of first-line retreatment of 63% (6). For pyrazinamide, only a few studies have directly evaluated the correlation between in vitro resistance with clinical outcomes (12,(29)(30)(31)(32). One of these reported that patients whose isolates had an MIC breakpoint of over 50 mg/liter had poor sputum conversion rates (12).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of rifampin, a prior study found that phenotypic DST does not capture some clinically relevant resistance conferred by disputed rpoB mutations that had previously been considered of indeterminate significance; these were associated with a rate of failure or relapse of first-line retreatment of 63% (6). For pyrazinamide, only a few studies have directly evaluated the correlation between in vitro resistance with clinical outcomes (12,(29)(30)(31)(32). One of these reported that patients whose isolates had an MIC breakpoint of over 50 mg/liter had poor sputum conversion rates (12).…”
Section: Discussionmentioning
confidence: 99%
“…The use of aminoglycosides is essential in MDR-TB treatment (20). However, pharmacokinetic monitoring is essential in selecting the optimal dose.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations up to 10 mg/liter (0.3, 0.5, 1.5, 3.0, 5.0, 7.0, and 10.0 mg/liter) were analyzed without a dilution step. Concentrations between 10 and 40 mg/liter were diluted 1:6 with deionized water (20,30, and 40 mg/liter). High concentrations (60 to 80 mg/liter) were diluted 1:12 before analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Data from research design to evaluate the mechanism and its guiding principles demonstrate the impact and effectiveness of the initiative since its launch. In one large multinational prospective cohort study evaluating treatment approaches and comparing outcomes for MDR-TB patients in countries using the GLC mechanism versus those that did not showed that treatment success among patients in countries using the mechanism was substantially greater [83% versus 60%, respectively; (p < 0.001)] and by extension the initiative was shown to have reduced further emergence of anti-TB drug resistance [52]. The GLC mechanism may be useful in the development of other partnerships needed in the rational allocation of resources and tools for combating AMR more broadly.…”
Section: Examples Of Stewardshipmentioning
confidence: 99%